Analisis Struktur dan Kebahasaan Editorial Tema Piala Dunia pada Media Bola.Net Edisi November 2022 dan Rekomendasinya sebagai Bahan Ajar Struktur dan Kebahasaan Teks Editorial Kelas XII SMA - Fransisca, Novi Diana; Setiawan, Hendra; Meliasanti, Ferina (IAI Nasional Laa Roiba Bogor, 2024)
Editorial text is a text or writing that raises an issue based on the point of view of a media. The writing is equipped with evidence, facts, and reasons that support to strengthen the arguments or opinions of the editor. This research aims to describe the structure and language feature of editorial texts with the theme of the World Cup in Bola.net media. In addition, this research also aims to describe the recommendations of the research results as teaching materials for editorial texts in grade 12 high school. This research uses a qualitative approach with a qualitative descriptive method. The data collection technique used was purposive sampling technique. In addition, documentation techniques and listening - note taking techniques were also used. The results showed that in 21 editorial texts on the theme of the 2022 World Cup on Bola.net media, all of them have a complete structure. The structure includes issue introduction, argumentation, and reaffirmation or recommendation. In terms of language, there are some texts that still do not fulfill the language feature. The results of the study are recommended as teaching materials for editorial text material for grade 12 high school. Teaching materials made, namely Learner Worksheets or LKPD.